2011
DOI: 10.1021/es200248d
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Occurrence and Removal of Pharmaceuticals and Personal Care Products in Different Biological Wastewater Treatment Processes

Abstract: The occurrence of 12 pharmaceuticals and personal care products (PPCPs) in two wastewater treatment plants in Beijing was studied monthly over the course of one year. The removal of PPCPs by three biological treatment processes including conventional activated sludge (CAS), biological nutrient removal (BNR), and membrane bioreactor (MBR) was compared during different seasons. Seasonal variations of PPCPs in the wastewater influent were discrepant, while in the wastewater effluent, most PPCPs had lower concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
113
5
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(146 citation statements)
references
References 35 publications
21
113
5
7
Order By: Relevance
“…Carbamazepine epoxide concentrations were below the LOQ (3 ng L À1 ) in all samples. The elimination of both CBMZDI and carbamazepine was limited (À13% to 45%) in the WWTPs, as found in other studies, due to the chemical inertness and weak adsorption of these compounds on sludge (Lin et al, 2009;Zhou et al, 2010;Sui et al, 2011;Bueno et al, 2012), as well as by the reformation from the conjugated forms by microbial activity during treatment (Miao et al, 2005).…”
Section: Antiepilepticssupporting
confidence: 63%
See 2 more Smart Citations
“…Carbamazepine epoxide concentrations were below the LOQ (3 ng L À1 ) in all samples. The elimination of both CBMZDI and carbamazepine was limited (À13% to 45%) in the WWTPs, as found in other studies, due to the chemical inertness and weak adsorption of these compounds on sludge (Lin et al, 2009;Zhou et al, 2010;Sui et al, 2011;Bueno et al, 2012), as well as by the reformation from the conjugated forms by microbial activity during treatment (Miao et al, 2005).…”
Section: Antiepilepticssupporting
confidence: 63%
“…These levels were 2-4 times higher than those found in our study although the elimination efficiencies were similar. Both studies used 24 h composite samples, so the differences observed for this compound could possibly be explained by seasonal variations in the raw wastewater (Sui et al, 2011;Gao et al, 2012b).…”
Section: Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBU and DIC) differs greatly 380 between cold and hot seasons (Sui et al, 2011;Vieno et al, 2005). As the sampling 381 campaign was carried out only in the hot season (end of spring and summer), the low 382 consumption of anti-inflammatory drugs when compared with yearly consumption may 383 result from the significant seasonal differences in their consumption.…”
Section: Consumption Assessment 361mentioning
confidence: 99%
“…Membrane bioreactor (MBR) treatment processes showed improved PPCP removal compared with CAS and biological nutrient removal processes (Sipma et al 2010;Sui et al 2011). Constructed wetlands based on shallow pond, beds, or trenches containing aquatic macrophytes are considered to be cost-effective in treating wastewater due to a relatively low cost in construction, operation, and maintenance (Wu et al 2015b).…”
Section: Introductionmentioning
confidence: 99%